Death and the aesthetic of continuity: reading Victor Hugo's Contemplations - Lunn-Rockliffe, K (Oxford University Press, 2008)
This article addresses the importance of continuity in Victor Hugo's poetry, understood both as connection between author and reader and as sheer length. Arguing that his very prolixity merits analysis, it investigates the relationship between his connective readability and his ability to sustain long verse paragraphs. It uses examples from the long visionary poem in book VI of Les Contemplations, which represent death both as a rupture and as a continuity. The first part considers the connection between poet and reader, focusing on Hugo's use of solitude as an experience shared by the dead, the poet and the reader. He plays on the concrete reality that the printed book is read in isolation to draw the reader close to the visionary experience of death. The second part examines how the reader is made to go through this solitary experience line by line, a process that unfolds in time. It shows how Hugo builds verse lines into a continuum and plays on turning points, particularly line-endings, to sustain his long verse paragraphs. Far from being monolithic blocks, these sequences are articulated by a series of transitions which constantly oblige the reader to reconsider the relationship between breaks and joinings, separation and continuity.